2018
DOI: 10.1186/s12889-018-6212-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-medical prescription stimulant use to improve academic performance among Australian university students: prevalence and correlates of use

Abstract: BackgroundSome university students consume pharmaceutical stimulants without a medical prescription with the goal of improving their academic performance. The prevalence of this practice has been well documented in the US, but less so in other countries. The potential harms of using prescription stimulants require a better understanding of the prevalence of this practice within Australian universities.MethodsAn internet survey of 1136 Australian students was conducted in 2015 in three large Australian universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 26 publications
4
44
1
12
Order By: Relevance
“…students preferred independent learning which shows that studying alone in silence increases concentration leading to enhanced learning and retention. Some international studies also found out an association between sleep quality and academic 16,17,18 performance. A study conducted at University of Newcastle, Australia showed a significant association between daily breakfast intake and 9 academic performance similar to our study.Healthy breakfast in the morning boosts up the energy level and opens up the pathways for learning and retention.…”
Section: Resultsmentioning
confidence: 92%
“…students preferred independent learning which shows that studying alone in silence increases concentration leading to enhanced learning and retention. Some international studies also found out an association between sleep quality and academic 16,17,18 performance. A study conducted at University of Newcastle, Australia showed a significant association between daily breakfast intake and 9 academic performance similar to our study.Healthy breakfast in the morning boosts up the energy level and opens up the pathways for learning and retention.…”
Section: Resultsmentioning
confidence: 92%
“…The number of students using prescription drugs to improve cognitive performance without medical indication has increased over the last years, in spite of the potential risks associated with this use (1). Prevalence rates of non-medical stimulant use of 8.3% (lifetime) and 5.9% (past-year) in a sample of 4,580 US college students (2), 4.3% (lifetime) in a representative sample of 1,128 adults in the German population (3), and a lifetime prevalence rate of 6.5% among Australian university students (4) have been reported…”
Section: Introductionmentioning
confidence: 99%
“…First, and as noted above, contributions in this issue are from scholars in Denmark, the UK and the United States, reflecting the existing dominance of Northern European and North American viewpoints in the field to date. There also has been some research into PCEDs in Australia and New Zealand (Jensen, Forlini, Partridge, & Hall, 2016;Lucke et al, 2018;Mazanov, Dunn, Connor, & Fielding, 2013;Partridge, Bell, Lucke, & Hall, 2013;Partridge, Bell, Lucke, Yeates, & Hall, 2011;Ram, Hussainy, Henning, Jensen, & Russell, 2016) and a small number of studies conducted in other cultural contexts such as South Africa (Beyer, Staunton, & Moodley, 2014) and Brazil (Ortega et al, 2010). However, the lack of attention given to PCEDs in other cultural contexts, such as China, South Asia and across African nations for example, is notable.…”
Section: Summary and Future Agendasmentioning
confidence: 99%